2015
DOI: 10.1039/c5ra12217a
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyethyleneimine as an additive in cyanide-free electrolytes for gold electrodeposition

Abstract: The influence of polyethyleneimine (PEI) on the electrochemical behavior of cyanide-free electrolytes with 5,5-dimethylhydantoin (DMH) as a complexing agent was investigated using cyclic voltammetry (CV), chronoamperometry, and cathodic polarization measurements. The gold electrodeposition displayed three-dimensional (3-D) progressive nucleation in both the absence and presence of PEI according to the Scharifer and Hills (SH) nucleation model. With the addition of PEI, the cathodic overpotential showed an imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…The almost doubling of a demonstrates that the electron transfer of the gold electrodeposition process was obviously inuenced by the DMH in the electrolyte as the complexing agent for Au 3+ . Following eqn (3) and the tted j p vs. v 1/2 plots, the diffusion coefficient (D) of ions in the electrolyte were calculated as 8.69 Â 10 À6 cm 2 s À1 and 4.19 Â 10 À6 cm 2 s À1 , 49 respectively, indicating that D was reduced with the addition of DMH in the electrolyte. It indicated that with DMH as the complexing agent for Au 3+ in the gold electroplating electrolyte, the ion transfer was inhibited.…”
Section: Kinetic Featuresmentioning
confidence: 99%
“…The almost doubling of a demonstrates that the electron transfer of the gold electrodeposition process was obviously inuenced by the DMH in the electrolyte as the complexing agent for Au 3+ . Following eqn (3) and the tted j p vs. v 1/2 plots, the diffusion coefficient (D) of ions in the electrolyte were calculated as 8.69 Â 10 À6 cm 2 s À1 and 4.19 Â 10 À6 cm 2 s À1 , 49 respectively, indicating that D was reduced with the addition of DMH in the electrolyte. It indicated that with DMH as the complexing agent for Au 3+ in the gold electroplating electrolyte, the ion transfer was inhibited.…”
Section: Kinetic Featuresmentioning
confidence: 99%
“…These results provide an indication that the surface quality of the gold electrodeposit could be further improved upon the addition of a suitable additive. 59 The phase structures of the gold electrodeposits that were obtained from the introduced cyanide-free gold electroplating electrolyte with and without additive, as well as those of the electrodeposits obtained from the HAuCl 4 electrolyte without DMH were conrmed using EDS and XRD. Unfortunately, when the additive was added to the HAuCl 4 electrolyte without DMH, the HAuCl 4 electrolyte became turbid and a precipitate was formed, as displayed in Fig.…”
Section: Function Of Dmh In Gold Electroplatingmentioning
confidence: 99%
“…In the XRD pattern of the catalyst (Figure ), the peaks indexed to Au (111), (200), (220), (311) and (222) crystal faces at 2 theta values of 38.2, 44.4, 64.6, 77.6 and 81.7 were obviously discovered (JCPDS file: 04–0784). The diffraction peak intensity of the (111) faces for gold is higher than that of any other peak, indicating that the reduction of Au (III) to Au occurred preferentially on Au (111) faces, as expected . It is clear that the typical silica is observed at a broad peak centered at 2θ = 22.5°, which indicates that the sample is semi‐crystalline phase…”
Section: Resultsmentioning
confidence: 52%